Pasteurella multocida involved in respiratory disease of wild chimpanzees. - Sophie Köndgen; Michaela Leider; Felix Lankester; Astrid Bethe; Antina Lübke-Becker; Fabian H Leendertz; Christa Ewers (PLoS ONE, 2011)
Pasteurella multocida can cause a variety of diseases in various species of mammals and birds throughout the world but nothing is known about its importance for wild great apes. In this study we isolated P. multocida from wild living, habituated chimpanzees from Taï National Park, Côte d'Ivoire. Isolates originated from two chimpanzees that died during a respiratory disease outbreak in 2004 as well as from one individual that developed chronic air-sacculitis following this outbreak. Four isolates were subjected to a full phenotypic and molecular characterisation. Two different clones were identified using pulsed field gel electrophoresis. Multi Locus Sequence Typing (MLST) enabled the identification of previous unknown alleles and two new sequence types, ST68 and ST69, were assigned. Phylogenetic analysis of the superoxide dismutase (sodA) gene and concatenated sequences from seven MLST-housekeeping genes showed close clustering within known P. multocida isolated from various hosts and geographic locations. Due to the clinical relevance of the strains described here, these results make an important contribution to our knowledge of pathogens involved in lethal disease outbreaks among endangered great apes.